About Onomasiologic-Mystical Conceptualization of the Bosniak Poetry in Oriental Languages - Kadrić, Adnan (Prilozi za orijentalnu filologiju, 2017)
This paper attempts to draw attention to the phenomenon of onomasiologic-mystical conceptualization of Bosniak poetry in Oriental languages at the example of Ahmed Wali Yenipazarli’s symbolic-mystical and love epic Beauty and Heart (Husn ü Dil) and Darwish Pasha Bajezidagić’s poem Muradname. It also draws attention to the fact that the process of mystical resemantization of poetry in Oriental languages was already completed at the time of classical Persian poetry and that the mentioned concept was transferred into Ottoman Empire and was finally present in numerous poetic works of Bosniaks in the 16th century. The comparison of “mystical image-ideas” (hıyal) in Ahmed Wali Yenipazarli’s and Darwish Pasha Bajezidagić’s narrative poetry indicates many systematic similarities in the mentioned works. The quotes from the Ahmed Wali Yenipazarli’s poetry suggest that the poet himself was aware of the concept on the basis of which he encodes his poetic expression at the semantic level.